2021
DOI: 10.5194/esd-12-1371-2021
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of compound hot–dry extremes on US soybean yields

Abstract: Abstract. The US agriculture system supplies more than one-third of globally traded soybean, and with 90 % of US soybean produced under rainfed agriculture, soybean trade is particularly sensitive to weather and climate variability. Average growing season climate conditions can explain about one-third of US soybean yield variability. Additionally, crops can be sensitive to specific short-term weather extremes, occurring in isolation or compounding at key moments throughout crop development. Here, we identify t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 89 publications
(131 reference statements)
2
30
0
Order By: Relevance
“…3 E,F)—all highly important regions for global soybean production. Noteworthy, for North America, also previous research has reported yield reductions during compound hot-dry events 43 .…”
Section: Resultsmentioning
confidence: 88%
“…3 E,F)—all highly important regions for global soybean production. Noteworthy, for North America, also previous research has reported yield reductions during compound hot-dry events 43 .…”
Section: Resultsmentioning
confidence: 88%
“…We find that summer soil moisture is strongly preconditioned by antecedent soil moisture in the SESA and US regions. Soil moisture memory can persist over several months which implies that spring anomalies can influence summer soil moisture conditions and in turn intensify summer land-atmosphere feedbacks (Anderson et al, 2017a;Hamed et al, 2021;Sippel et al, 2018;Sippela et al, 2016). The lack of a significant relationship between antecedent (spring) and summer soil moisture in the CB region could be related to local land-atmosphere feedbacks, which can force an inverse relationship between austral spring and summer moisture conditions particularly during ENSO events (Grimm et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…1a). Wisconsin, Michigan, Minnesota and North and South Dakota are omitted from the US cluster as these northern states were previously shown to have a different seasonal climate sensitivity compared to the rest of the US regions considered (Hamed et al, 2021;Schauberger et al, 2017). Weighted spatial average timeseries are calculated at regional level for the three defined regions https://doi.org/10.5194/egusphere-2022-960 Preprint.…”
Section: Soybean Yield Datamentioning
confidence: 99%
See 1 more Smart Citation
“…Temperature, precipitation and their interaction are often used to predict crop yields with statistical models (e.g., Lobell & Field, 2007; Luan et al, 2021; Matiu et al, 2017; Ray et al, 2015), explaining approximately a third of crop yield variability globally, with large local variations (Ray et al, 2015). Several aspects of the crop response to precipitation and temperature are mediated by soil water availability (e.g., Hamed et al, 2021; Luan & Vico, 2021; Riha et al, 1996), making soil moisture a better predictor of yields (Proctor et al, 2022). Soil moisture data are unavailable for long periods and over wide geographical areas, limiting robust statistical inference.…”
Section: Introductionmentioning
confidence: 99%